.6-0.25f=f-3

Simple and best practice solution for .6-0.25f=f-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .6-0.25f=f-3 equation:


Simplifying
0.6 + -0.25f = f + -3

Reorder the terms:
0.6 + -0.25f = -3 + f

Solving
0.6 + -0.25f = -3 + f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1f' to each side of the equation.
0.6 + -0.25f + -1f = -3 + f + -1f

Combine like terms: -0.25f + -1f = -1.25f
0.6 + -1.25f = -3 + f + -1f

Combine like terms: f + -1f = 0
0.6 + -1.25f = -3 + 0
0.6 + -1.25f = -3

Add '-0.6' to each side of the equation.
0.6 + -0.6 + -1.25f = -3 + -0.6

Combine like terms: 0.6 + -0.6 = 0.0
0.0 + -1.25f = -3 + -0.6
-1.25f = -3 + -0.6

Combine like terms: -3 + -0.6 = -3.6
-1.25f = -3.6

Divide each side by '-1.25'.
f = 2.88

Simplifying
f = 2.88

See similar equations:

| 4ln(x)-ln(x^4)= | | Y=.5(3)+1 | | 2x-3x+x+9x=2-4+35 | | 2x^3+2x^2-72=0 | | -10(p+8)=110 | | -27+v=-12 | | -5-5x+6x=6 | | 5e^6+7=12 | | -2.7x+4(x-1)=10.5(2x+6)+31.5 | | -(5a+5)-3(a-6)= | | 48+6x=90 | | 5e^1+7=12 | | 9x+1=3x-13 | | 2x+6.8+8x+1.4+x=90 | | 3s^2-26s-9= | | 8p+7=13+7p | | -2(1-4x)=6x+12 | | 7(7x-1)-18=47x+7 | | 8b=2b | | 64c^2-16=0 | | 5(2x-4)=0 | | -8(x+3)+2x+5=7x+9 | | 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x | | 2c-7=18 | | .8x-.2y-.1x-1.2y=.7 | | y-3/3-y-2/2=-1 | | 18/65=x/35 | | 9(q+9)= |

Equations solver categories